Adsorption Equilibrium and Mechanism and of Water Molecule on the Surfaces of Molybdenite (MoS2) Based on Kinetic Monte-Carlo Method - Ruilin Wang; Xinyu Wang; Zhijun Zuo; Shijun Ni; Jie Dai; Dewei Wang (Molecules, 2022)
The oxidation/weathering of molybdenite (MoS2) is too slow to be monitored, even under pure oxygen and high temperatures, while it proceeds rapidly through humid air. The adsorption of water molecules on molybdenite is necessary for the wet oxidation/weathering of molybdenite. Therefore, we employ kinetic Monte Carlo modeling to clarify the adsorption isotherm, site preferences and kinetics of water on different surfaces of molybdenite. Our results indicate that (1) the adsorption capacity and adsorption rate coefficient of H2O on the (110) surface are significantly larger than those on the (001) surface at a temperature of 0~100 °C and a relative humidity of 0~100%, suggesting that the (110) surface is the predominant surface controlling the reactivity and solubility of molybdenite in its interaction with water; (2) the kinetic Monte Carlo modeling considering the adsorption/desorption rate of H2O, dissociation/formation rate of H2O and adsorption/desorption of dissociated H indicates that the adsorption and dissociation of H2O on the (110) surface can be completed in one microsecond (ms) at 298 K and in wet conditions; (3) the adsorption and dissociation of H2O on molybdenite are not the rate-limiting steps in the wet oxidation/weathering of molybdenite; and (4) kinetic Monte Carlo modeling explains the experimental SIMS observation that H2O and OH (rather than H+/H− or H2O) occupy the surface of MoS2 in a short time. This study provides new molecular-scale insights to aid in our understanding of the oxidation/weathering mechanism of molybdenite as the predominant mineral containing molybdenum in the Earth’s crust.